Adaptive speed/position control of induction motor based on SPR approach - Lee, Hou-Tsan (International journal of control, 2014)
A sensorless speed/position tracking control scheme for induction motors is proposed subject to unknown load torque via adaptive strictly positive real (SPR) approach design. A special nonlinear coordinate transform is first provided to reform the dynamical model of the induction motor. The information on rotor fluxes can thus be derived from the dynamical model to decide on the proportion of input voltage in the d-q frame under the constraint of the maximum power transfer property of induction motors. Based on the SPR approach, the speed and position control objectives can be achieved. The proposed control scheme is to provide the speed/position control of induction motors while lacking the knowledge of some mechanical system parameters, such as the motor inertia, motor damping coefficient, and the unknown payload. The adaptive control technique is thus involved in the field oriented control scheme to deal with the unknown parameters. The thorough proof is derived to guarantee the stability of the speed and position of control systems of induction motors. Besides, numerical simulation and experimental results are also provided to validate the effectiveness of the proposed control scheme.